Assessment of donor return following temporary deferral in camp as well as in-house donors) in a blood bank attached to tertiary care hospital - Mulla, Faruq Ibrahimbhai; Inaniya, Kailash Sukhram (International Journal of Research in Medical Sciences, 2017)
Background: In India, about 60% of donation is through voluntary blood donors. However, about one third already motivated blood donors are deferred due to stringent screening criteria, either temporarily or permanently. The temporarily deferred donors could be a good source of blood donation after deferral period. The objective of this study was to know the main causes of pre-donation deferral in potentially healthy prospective blood donors, to investigate impact of deferral on donation pattern and to evaluate impact of post deferral counseling on donation pattern. Methods: The present study is carried out in A. D. Gorwala blood bank in Anand, Gujarat from April 2014 to September 2015. All donors screened as per the guideline and deferred donors are categorized as temporary and permanently deferred donors. A Comparison group of healthy eligible donors who donate blood at ADGBB is also studied to determine impact of deferral on donation pattern. From temporarily deferred donors, reason for deferral is considered. At the time of deferral, donors properly counseled, clearly informed about the reason of deferral and corrective actions are taken. As per reason of deferral, time duration for recalling the donor is defined. Based on this, donor is called back to donate again for up to six month’s period after expiration of deferral period. Results: Total 12.57% donors were deferred temporarily. Significant female preponderance was observed (58.7% vs 8.90%). Low hemoglobin (60.9%) was the most common reason of temporary deferral followed by abnormal BP and medicine ingestion. Total 378 donors were responded back out of 953 of deferred donors compare to 645 in non-deferred group. Middle age, male, repeat donors, in-house donors, high education, high socio-economic status, shorter duration of deferral appears to significantly predict donor return. In the evaluation of reasons of the re-deferral, Low hemoglobin was the prime reason. Unfavourable location, lack of time and change in job/college are major barrier to donor return. Total 39.60% response observed after post deferral counseling in present study compared to 11.20% in year 2013-2014. Conclusions: Efforts to increase the hemoglobin will improve the donor retention and overall blood safety can be increased. Temporary deferral has negative impact on donor return and duration of response after expiration of deferral, both in first time and repeat donors. Interventions to increase return behavior need to be better targeted at specific donor groups and it should be developed according to major barriers to donor return prevalent in particular region mainly through more effective communication with donors. Education, motivation, post deferral counseling.